UiTM Seremban 3 students’ habits and attitude on the use of ChatGPT for academic purposes / PM Dr Alice Shanthi Kasawi @ Krisnan, Sheela Paramasivam and Nur Amirah Nabihah Zainal Abidin - Kasawi @ Krisnan, Alice Shanthi; Paramasivam, Sheela; Zainal Abidin, Nur Amirah Nabihah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Nowadays, Artificial Intelligence (AI) is a key component of the popular social networks being used by many. Artificial Intelligence (AI) is increasingly permeating the educational landscape, with many experts viewing it as a driving force behind the industrial and educational revolutions (Huang et al., 2021). One such AI technology making waves is ChatGPT, an advanced chatbot developed by OpenAI in late 2022. This cutting-edge natural language processing system can comprehend and respond to student inquiries in a remarkably human-like manner. Within just two months of its launch, ChatGPT garnered an impressive 100 million active users, underscoring its rapid adoption and potential (Hu, 2023). In the era of digital learning and remote education, ChatGPT offers a promising solution to enhance the educational experience by providing a personalised, tailored approach to meet individual student needs (Chatterjee & Bhattacharjee, 2020).